(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In 2019-2022, an employee of the archeology department of the IHAE NAS KR Sultanov E.K., at the invitation of a resident of the village Kyzyl-Suu, Ergeshov Turdumamat and his own funding, reconnaissance work was carried out in the lower reaches of the river Gulcho, in the vicinity of the village Kyzyl-Suu. One of the tasks was to identify new archaeological monuments, describe, photograph and, if possible, compile a visual planigraphy of the monuments. In this territory, various types of monuments have been identified, belonging to different chronological periods - from the Bronze Age to the Middle Ages.